Falciform Anemia: Conception of the family caregiver about the disease and its treatment in a City in Maranhão (Research, Society and Development, 2021)
Introduction: Sickle cell anemia - AF is a genetic alteration, since hemoglobin mutation occurs, designated as hemoglobin S or HbS. Objective: to know the conception of the family caregiver of the PA patient about the disease and its treatment in the city of Colinas. Methodology: This is a descriptive study with a qualitative approach, carried out in the municipality of Colinas - MA, from May to June 2019. Where semi-structured questionnaires were used as a data collection instrument. Results and Discussion: Eight (8) responsible for sickle cell anemia patients were interviewed, of the eight (8), six (6) is the mother of the carrier, one (1) is the grandmother and one (1) is the great-grandmother of the child , age 25 to 64 years. When asked about ethnicity, 75% considered themselves brown, 12.5% ​​black and 12.5% ​​white; on family income 12.5% ​​declared to receive two minimum wages, 62.5% live on one minimum wage and 25% live on less than one minimum wage; when asking about education, 50% have not completed elementary school, 25% have incomplete high school and 25% have completed high school; on the number of children 37.5% have three (3) children, 37.5% have two (2) children and 25% only one (1) child. Conclusion: In this study, it was analyzed that the municipality does not provide all the centers that integrate the treatment of sickle cell disease.